Site Selection for Hazardous Waste Using FuzzyLogic Combined With Analytic Hierarchy Process: ACase study in Nahavand, Iran - Abbas Najjari; Kamran Shayesteh (Hamadan University of Medical Sciences, 2019)
Hazardous wastes include various types of chemicals and other wastes generated from industrialand other sources. Because of the complexity of waste management systems, the selection of theappropriate solid waste landfill site requires consideration of multiple alternative solutions andevaluation criteria. This paper investigated the utilization of the fuzzy logic in combination withAnalytic Hierarchy Process (AHP) technique by applying GIS and IDRISI programming for choosinghazardous waste landfill site in Nahavand, Iran. Based on the real conditions of the study area, weconsidered economic, biological and topographical factors (12 criteria). The candidate sites weredetermined based on the criteria weights. The best location was determined via the fuzzy logic andthe AHP methods. This study found that the combination of fuzzy logic and the AHP method was thebest option for selecting a site for hazardous waste landfill. In the end, 6 suitable areas were selectedfor a hazardous waste landfill in the city. This study verified that the combination of the AHP methodwith fuzzy logic using GIS in our project is a powerful tool for solid waste landfill site selection.